Spaces of Spanish university. A historical reading - Hernández Díaz, José María (CIAN-Revista de Historia de las Universidades, 2014)
Spanish contemporary university offers a very diverse and heterogeneous external and internal spatial image, resulting from the break traditional teaching models and the incorporation of new missions to research, to new teaching and non-contact digital formats, and the service applicant large sections of youth population. The spaces at the university can only be understood within the historical contexts that define them, conditioned by many variables that require explanation. Today the EHEA also raises many questions in regards to spaces and campus.